Investigation into UHI monitoring with GNSS sensor network - Mendez Astudillo, Jorge (2020)
Radio frequency (RF) signals are used in Global Navigation Satellite Systems (GNSS) for positioning applications, however, it can also be used to monitor the atmosphere. RF signals can be affected by changes in the atmospheric refractivity index along their propagation path. This change of refractive index along the path of the signal in the troposphere causes a delay to the signal known as the Tropospheric Delay (TD). The TD in the zenith direction (ZTD) has already been used to derive the amount of precipitable water at a given site because the refractive index of air in the atmosphere is proportional to the environmental variables: temperature (T), pressure (P) and water vapour partial pressure (e). However, other environmental variables such as T have not been derived from the ZTD. Thus, this thesis presents a novel algorithm to estimate temperature from GNSS data for monitoring urban heat island intensity (UHII). An urban heat island (UHI) occurs when an urban area is warmer than its adjacent rural areas. It exacerbates heat waves, leading to increased energy consumption and adverse effects to the environment and to human health. UHIs are monitored using remote sensing techniques, which allow the monitoring of large geographical areas with low time resolution. However, the study of UHIs within a city requires better spatial and temporal resolution. It is also desired to monitor the UHI in real-time. The algorithm presented in this thesis allows UHI monitoring with higher spatial and temporal resolution using a GNSS network.